Cluster approach to formation of nitrogen–rare gas cryoalloys - Solodovnik, A.A.; Danchuk, V.V.; Mysko, N.S. (Физика низких температур, 2013)
Structure of solid binary N₂–Kr and N₂–Ar solutions were studied by transmission electron diffraction (THEED). The samples were prepared in situ by deposition of gaseous mixture onto an Al substrate cooled to 20 K. The lattice parameters for low concentrations of one of the components were measured. The relative change of the lattice parameter per unit concentration is determined for N₂ impurity in Kr and Ar as well as for Kr and Ar in N₂. Analysis of the concentration dependence of the lattice parameters for low fractions of both components was performed within a cluster model in the three-particle approximation.